Pengaruh Corporate Social Responsibility, Struktur Aktiva, Pertumbuhan Aset Dan Pertumbuhan Penjualan Terhadap Kinerja Perusahaan - Free Antonius Simanjuntak (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The purpose of this research is to determine and analyze the effect of corporate social responsibility, asset structure, asset growth and sales growth on company performance. The research population used is data on corporate social responsibility, asset structure, asset growth and sales growth on company performance. The sampling technique was saturated due to this research using data from corporate social responsibility, asset structure, asset growth and sales growth on company performance period January 2017 - June 2020. Researchers used documentation study data collection techniques to collect this research data. The result showed that corporate social responsibility has no effect on company performance . Asset structure affects company performance . Asset growth has no effect on company performance. Sales growth has no effect on company performance . Simultaneously corporate social responsibility, asset structure, asset growth and sales growth have an effect on company performance